Teacher autonomy support and externalizing problems: Variations based on growth mindset toward personality and ethnicity - Ma, Yongfeng; Ma, Chunhua; Lan, Xiaoyu (Frontiers in Psychology, 2022)
Given the prevalence of externalizing problems during adolescence, the present study investigated the main and interactive relationships between environmental-level (teacher autonomy support) and person-level (growth mindset toward personality) factors related to externalizing problems. This study further estimated ethnic variations of these relationships among the majority Han and one Muslim ethnic minority group (Hui) in China. To achieve the research objectives, the study involved 704 Han (M age = 12.57; 53.7% female) and 642 Hui adolescents (M age = 12.45; 49.4% female) who completed a suite of research questionnaires. The results of the hierarchical linear regression analysis, after controlling for sociodemographic characteristics and comorbid internalizing problems, showed that teacher autonomy support was directly and adversely related to externalizing problems. This inverse relationship was also moderated by growth mindset toward personality and ethnicity. More specifically, a high growth mindset buffered the undesirable effect of low teacher autonomy support on externalizing problems for Hui adolescents but not Han adolescents. The finding from the current research suggests that teacher autonomy support plays a universally beneficial role in youth mental health across two selected ethnic groups. At the same time, identifying the protective role of growth mindset has important practical implications for the design of personalized school-based activities that aim to facilitate adaptive youth behaviors.